Validación Inter-operador de Videobserver™ - Fortes, A.M.; Gómez, M.A.; Hongyou, L.; Sampedro, J. (Cuadernos de Psicología del Deporte, 2016)
The purpose of this study was to evaluate the degree of interobserver reliability for the sport analysis company VIDEOBSERVER™. The football match corresponding to the 2014 World Cup final was used as the sample for the study. Data were collected on 28 players, including the actions of the goalkeepers and the players substituted during the match. This study was carried out in four phases: (i) a revision of the literature was performed to define the theoretical frame-work and the procedures to be followed; (ii) an observation system was created with the help of two experienced sports analysis technicians; (iii) a pilot study was carried out with the aim of verifying the operativity of the observation system; and (iv) the main study of inter-observer reliability was developed. The values of the kappa index, the standardized typical error and the intra-class correlation coefficient were used for the statistical analysis. The results showed a high level of inter-operator reliability, a statement which is supported by the high values of the intra-class correlation coefficient (both at the individual and collective level) and the small standardized typical error which were found in this study. This study adds an innovative element of analysis consisting in the fact that the evaluation was carried out not only at the collective level but also at the individual level.